2017
DOI: 10.1016/j.neuropharm.2017.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairments associated with alterations in synaptic proteins induced by the genetic loss of adenosine A 2A receptors in mice

Abstract: The study of psychiatric disorders usually focuses on emotional symptoms assessment. However, cognitive deficiencies frequently constitute the core symptoms, are often poorly controlled and handicap individual's quality of life. Adenosine receptors, through the control of both dopamine and glutamate systems, have been implicated in the pathophysiology of several psychiatric disorders such as schizophrenia and attention deficit/hyperactivity disorder. Indeed, clinical data indicate that poorly responsive schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…We found that A 2A R activation and ENT1 inhibitor could improve neurodegeneration in aging. Our results are complementary to Moscoso-Castro et al, who found that deletion of A 2A R led to deficits in spatial memory and learning as well as decreased neurogenesis [ 41 ]. However, A 2A R activation or inhibition as a benefit for anti-aging is controversial [ 14 , 42 ].…”
Section: Discussionsupporting
confidence: 86%
“…We found that A 2A R activation and ENT1 inhibitor could improve neurodegeneration in aging. Our results are complementary to Moscoso-Castro et al, who found that deletion of A 2A R led to deficits in spatial memory and learning as well as decreased neurogenesis [ 41 ]. However, A 2A R activation or inhibition as a benefit for anti-aging is controversial [ 14 , 42 ].…”
Section: Discussionsupporting
confidence: 86%
“…Animals were killed 30 min after the cocaine‐primed reinstatement session, and PFC and STR were extracted, quickly frozen in dry ice and stored at −80°C until used for western blotting, as previously described (Moscoso‐Castro, López‐Cano, Gracia‐Rubio, Ciruela, & Valverde, ). In addition, PFC and STR were extracted in cocaine‐naïve animals to analyse GluA1 and GluA2 levels at basal conditions (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Moscoso-Castro, López-Cano, Gracia-Rubio, Ciruela, & Valverde, 2017). In addition, PFC and STR were extracted in cocaine-naïve animals to analyse GluA1 and GluA2 levels at basal conditions (seeSupporting Information).…”
mentioning
confidence: 99%
“…The adenosine hypothesis of schizophrenia [13,14] was recently bolstered by the observation that A 2A R deletion (A 2A R -/-) prompts behaviours that mimic symptoms of psychosis and molecular/anatomical alterations in mice, resembling the relevant phenotype features of the human disorder [23,27,28]. We first validated the A 2A R -/-based animal model of psychotic symptoms by comparing it with the well-established PCP animal model of sensory gating impairment of schizophrenia [19,29,30].…”
Section: Alterations In Sensorimotor Gating In Pcp Treated Animals Anmentioning
confidence: 99%